From acoustic waves to microwaves - Pacheco, Gefeson Mendes; Sakamoto, João Marcos Salvi; Kitano, Claudio [UNESP] (Polish Acad Sciences Inst Physics, 2015)
We present here some results of our research related to the optoelectronics and photonics and show all the experimental setups used. Starting with a discussion on the importance of the waves, we demonstrate our achievements based on employment of acoustic, optical, and microwaves and their technological use. The results concern the acousto-optic and electro-optic effects. The generalized analysis of the electro-optic effect reveals a new high induced birefringence in lithium niobate. A patented optical fiber microphone is presented, and its applications to the measurements of acoustic wave velocity in gases and in the laser ultrasound non-destructive evaluation system are discussed. Finally, the generation of microwaves by an optical method with substantial cost reduction is presented.